2019
DOI: 10.1681/asn.2018080808
|View full text |Cite
|
Sign up to set email alerts
|

Matching Human Unilateral AKI, a Reverse Translational Approach to Investigate Kidney Recovery after Ischemia

Abstract: BackgroundThe duration of renal ischemia that is associated with (or leads to) renal injury in patients is uncertain, and a reverse translational research approach has been proposed to improve animal models of AKI to facilitate clinical translatability. We developed a two murine models of unilateral renal ischemia to match a recently published human study that investigated renal injury after unilateral renal ischemia during partial nephrectomy.MethodsEight 10-week-old C57BL/6 male mice underwent left UiAKI or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Imaging software (Image J) was used to calculate the percent area of polarization. Immunohistochemistry for collagen type 3 was performed following standard protocols using goat anti-type III collagen antibody (Cat # 1330-01, Southern Biotech, Birmingham, Alabama [1:100]), followed by rabbit antigoat horseradish peroxidase (Ref # P0449, Dako, Carpinteria, California [1:200]) and analyzed as described previously ( 29 ). Both kidneys were analyzed for PSR and collagen 3, and the average was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging software (Image J) was used to calculate the percent area of polarization. Immunohistochemistry for collagen type 3 was performed following standard protocols using goat anti-type III collagen antibody (Cat # 1330-01, Southern Biotech, Birmingham, Alabama [1:100]), followed by rabbit antigoat horseradish peroxidase (Ref # P0449, Dako, Carpinteria, California [1:200]) and analyzed as described previously ( 29 ). Both kidneys were analyzed for PSR and collagen 3, and the average was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Kidneys were homogenized and analyzed using 1× RIPA buffer (Cell Signaling Technology, Danvers, Massachusetts) with either α-smooth muscle actin (SMA) primary antibody (ab32575, Abcam, Cambridge, United Kingdom, 1:5000) or KIM-1 Primary antibody (Cat#: AF1817, R and D Systems, Minneapolis, Minnesota, 1:1000) as previously described ( 29 ). Blots were normalized using the Revert Total Protein Stain (Cat # 926-11010, Licor, Lincoln, Nebraska) as a loading control and performed following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, serum creatinine level may not completely reflect the loss of kidney function during early stages [9]. Further, considering the ethical and regulatory obstacles related to human clinical studies, many studies on AKI have been conducted as observational or treatment research using murine animals [10][11][12][13]. These animal models of AKI mostly include young male mice with normal kidney functions that are evidently different from the actual clinical condition in human patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…64 A single-centre study in 30 paediatric patients (1-6 years old) who underwent cardiac surgery reported lower GFR and higher AKI incidence based on serum creatinine measurements obtained 5 minutes and 2 hours after weaning from cardiopulmonary bypass. [66][67][68] Their use in studies on the role of sympathetic activation may improve translatability of experimental data. In contrast to experimental renal IR studies where conditions can be well standardized, the effects of sympatholytics may have been blurred by the complexity of clinical scenarios and factors such as patient age, genetic diversity, associated chronic diseases and diverse co-medications.…”
Section: Of 10mentioning
confidence: 99%
“…3 Currently, reverse translational approaches are taken to better match animal models of renal IR to clinical situations that cause AKI. [66][67][68] Their use in studies on the role of sympathetic activation may improve translatability of experimental data.…”
Section: Clinical Akimentioning
confidence: 99%